Levels of Heavy Metals in Popular Cigarette Brands and Exposure to These Metals via Smoking - Muhammad Waqar Ashraf (The Scientific World Journal)
The levels of selected heavy metals in popular cigarette brands sold and/or produced in Saudi Arabia were determined by graphite furnace-atomic absorption spectrometry (GFAAS). Average concentrations of Cadmium and Lead in different cigarette brands were 1.81 and 2.46 μg g−1 (dry weight), respectively. The results obtained in this study estimate the average quantity of Cd inhaled from smoking one packet of 20 cigarettes to be in the range of 0.22–0.78 μg. Results suggest that the quantity of Pb inhaled of smoking one packet of 20 cigarettes is estimated to be 0.97–2.64 μg. The concentrations of Cd and Pb in cigarettes were significantly different between cigarette brands tested. The results of the present study were compared with those of other regional and international studies.